2017
DOI: 10.18632/oncotarget.14769
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional suppression of microRNA-27a contributes to laryngeal cancer differentiation via GSK-3β-involved Wnt/β-catenin pathway

Abstract: miR-27a regulates cell differentiation in a variety of diseases. However, whether and how miR-27a participates in laryngeal cancer cell differentiation remains unknown. Therefore, we explored role and molecular mechanism of miR-27a in laryngeal cancer differentiation in the study. We found that miR-27a expression was inversely correlated with laryngeal cancer differentiation degree based on the clinical pathological diagnosis of each patient. miR-27 asignificantly rescued differentiation and inhibited β-cateni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 30 publications
0
16
0
1
Order By: Relevance
“…provided evidence indicating that gastric cancer cell‐derived exosomal miR‐27a modulated transformation of fibroblasts into cancer‐associated fibroblasts. Most importantly, the radical involvement of miR‐27a in gastric cancer has been extensively investigated and a range of target genes have been identified . Zhou et al .…”
Section: Discussionmentioning
confidence: 99%
“…provided evidence indicating that gastric cancer cell‐derived exosomal miR‐27a modulated transformation of fibroblasts into cancer‐associated fibroblasts. Most importantly, the radical involvement of miR‐27a in gastric cancer has been extensively investigated and a range of target genes have been identified . Zhou et al .…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence to suggest that miRNA expression changed the across different species from miRNAs in many models of myocardial I/R injury, demonstrating the pivotal role of miRNAs in myocardial ischemic injury . It has been proposed that miR‐27 regulates cell differentiation in many diseases . It has conclusively been shown that miR‐27 may be involved in occurrence and development of atherosclerosis .…”
Section: Discussionmentioning
confidence: 99%
“…1,18 It has been proposed that miR-27 regulates cell differentiation in many diseases. 19,20 It has conclusively been shown that miR-27 may be involved in occurrence and development of atherosclerosis. 19 However, there were no reports on miR-27 acting a role in myocardial ischemic injury.…”
Section: Downregulated Expression Of Mir-27 In Myocardial Ischemia mentioning
confidence: 99%
“…It has been previously demonstrated that miR-27 can regulate the expression of genes involved in cell metabolism, differentiation, apoptosis, migration and immunity (29,30); On the other hand, an abnormal expression of miR-27 has been found in a variety of tumors and diseases (31)(32)(33). miR-27 regulates cell apoptosis, cell cycle progression and cell proliferation, as well as processes via the post-transcriptional regulation of different molecules, which indicates that miR-27 is a key molecule in the development of tumors (30,34). Pan et al demonsrated that miR-27a promoted osteosarcoma cell proliferation, migration and invasion (33).…”
Section: Introductionmentioning
confidence: 99%